2021
DOI: 10.1097/corr.0000000000001728
|View full text |Cite
|
Sign up to set email alerts
|

Has the COVID-19 Pandemic Changed the Daily Practices and Psychological State of Orthopaedic Residents?

Abstract: Background The coronavirus-19 (COVID-19) pandemic has been an unprecedented time for healthcare and has substantially changed resource availability in surgeons’ work practices and routines. Many orthopaedic departments suspended elective surgery, and some re-deployed orthopaedic residents to stressful nonorthopaedic tasks; long hours were commonplace. Stress-reaction symptoms such as anxiety and depression have been reported in about 10% of healthcare workers during previous infectious-diseases out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Chene et al (2021) results (n-T1:1565, n-T2:1109) showed that after lockdown, no significant changes were observed in the prevalence of depression and anxiety. Consistent with this, Castioni et al (2021)’s result (n=272) showed that the prevalence of anxiety remained the same but the prevalence of depression significantly increased after lockdown.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Chene et al (2021) results (n-T1:1565, n-T2:1109) showed that after lockdown, no significant changes were observed in the prevalence of depression and anxiety. Consistent with this, Castioni et al (2021)’s result (n=272) showed that the prevalence of anxiety remained the same but the prevalence of depression significantly increased after lockdown.…”
Section: Resultssupporting
confidence: 63%
“…18 datasets conducted in 11 countries during COVID-19 reported the prevalence of probable mental health disorders across different timepoints (details in S10 Appendix) (Algattas et al, 2021; Baumann et al, 2021; Cai et al, 2020; Castioni et al, 2021; Chene et al, 2021; De Kock et al, 2022; Doulias et al, 2021; Gündoĝmuş et al, 2021; Katsuta et al, 2021; Lasalvia et al, 2021; Lasalvia et al, 2020; Li et al; Magnavita et al, 2021a, b; Magnavita et al, 2020; Moore et al, 2021; Mosolova et al, 2021; Noaimi et al, 2021; Schmid et al, 2021; Shechter et al, 2021; Th’ng et al, 2021). Due to the variation in timepoints, differences in context, and the small number of studies, the temporal relationship between prevalence rates of mental health outcomes and the COVID-19 pandemic were narratively synthesised to avoid combining quantitative data inappropriately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results are in line with those reported by previous similar cross-sectional study on psychological state of residents. Indeed, the study that examined the psychological impact of COVID-19 on Italian orthopedic residents found that the pandemic had an important social impact on residents' perceptions and emotional well-being ( 42 ), manifesting in the worsening by the HADS score and the depression subscale of this score after the national lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…As part of these measures, all healthcare professionals have and continue to fight the COVID-19 infection alongside their primary duties, through regulations and decree laws. Although elective surgeries were stopped during the first and second waves, orthopedic residents continued to manage trauma patients while at the same time caring for COVID-19 patients and were inevitably affected both physically and psychologically during this process (5). Moreover, increasing patient burden and intense work pace also augmented these effects (6,7).…”
Section: Introductionmentioning
confidence: 99%